EFL Learning Strategies Employed by Indonesian Successful High School Students - Maharani Khansa (Jurnal Pendidikan Humaniora, 2020)
Abstract: Language learning strategies (LLSs) play an essential role in the process of English language learning. This study is aimed at investigating language-learning strategies employed by successful Indonesian EFL high school students. This study is of significance to provide a model of strategies practiced by successful EFL students who manage to develop good command of English regardless certain limitations and challenges they face. The results of this study show the students actively employ a combination of affective and cognitive-social learning strategies to develop their English skills.Keywords: language learning strategies, successful EFL learners, language learning, high schoolAbstrak: Strategi pembelajaran bahasa (LLS) memainkan peran penting dalam proses pembelajaran bahasa Inggris. Penelitian ini bertujuan untuk menyelidiki strategi pembelajaran bahasa yang digunakan oleh siswa EFL sekolah menengah atas di Indonesia yang berhasil. Studi ini sangat penting untuk memberikan model strategi yang dipraktikkan oleh siswa EFL yang berhasil yang berhasil mengembangkan penguasaan bahasa Inggris yang baik terlepas dari batasan dan tantangan tertentu yang mereka hadapi. Hasil penelitian ini menunjukkan siswa secara aktif menggunakan kombinasi strategi pembelajaran afektif dan kognitif-sosial untuk mengembangkan kemampuan bahasa Inggris mereka.Kata kunci: strategi pembelajaran bahasa, pebelajar bahasa Inggris EFL sukses, pembelajaran bahasa, siswa SMA